KEPEMIMPINAN KEPALA SEKOLAH DAN KUALIFIKASI AKADEMIK GURU TERHADAP KINERJA GURU (Studi Kasus di SDIT Ulul Albab Purworejo) - Lailla Hidayatul Amin (Institut Islam Mamba'ul 'Ulum Surakarta, 2019)
This study aims to reveal the influence of teachers' perceptions of school leadership and academic qualifications of teachers on teacher performance SDIT Ulul Albab 1 and 2 Purworejo. The approach used in this study is the quantitative approach. The research sample is determined by the formula nomogram Herry King. A population of 58 people with 95% confidence interval, are used to determine 56 people. Based on the results of the descriptive statistical analysis of the variables of school leadership gained a mean of 3.1379, academic qualifications obtained by mean of 2.4483 and teacher performance obtained by mean of 3.8276. There is a positive and significant impact of school leadership on teacher performance of 5.5%. There are no significant negative influence and academic qualifications of teachers on teacher performance of (-) 2.1%. There is the influence of positive and significant impact of school leadership and teachers' academic qualifications together on teacher performance by 0.4%.